PEMANFAATAN OPENSOURCE FREEWARE AUDACITY SEBAGAI PENDUKUNG MEDIA EDUKASI - Dyah Murwaningrum; Rena Amalika Asyari (INFOKOM (Informatika & Komputer), 2019)
Technological movement has influenced the learning methods of society. Lately, Instant learning becomes habit, but actually the depth learning is still needed. Professional instructors can teach and share the deep knowledge with audio.Playback and listen anytime are benefit of audio. Student and teacher will have flexible and efficient learning.Usingaudio method of Digital Audio Workstation software, this article aims to analyze and describe the effectivityaudio production for education. This paper focused to examineAudacity software as facilitator in audio production.